2022
DOI: 10.1177/00031348221101488
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence and Machine Learning in Prediction of Surgical Complications: Current State, Applications, and Implications

Abstract: Surgical complications pose significant challenges for surgeons, patients, and health care systems as they may result in patient distress, suboptimal outcomes, and higher health care costs. Artificial intelligence (AI)-driven models have revolutionized the field of surgery by accurately identifying patients at high risk of developing surgical complications and by overcoming several limitations associated with traditional statistics-based risk calculators. This article aims to provide an overview of AI in predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 38 publications
0
8
0
2
Order By: Relevance
“…These points are consistent with current research and developments in surgery and provide a comprehensive overview of AI's potential in surgery. [2][3][4][5] Furthermore, ChatGPT provided a brief but comprehensive history of AI in surgery, highlighting key milestones and developments during the past few decades. This helps to provide context and understanding of AI's progression in surgery, allowing readers to better understand its current state and potential future developments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These points are consistent with current research and developments in surgery and provide a comprehensive overview of AI's potential in surgery. [2][3][4][5] Furthermore, ChatGPT provided a brief but comprehensive history of AI in surgery, highlighting key milestones and developments during the past few decades. This helps to provide context and understanding of AI's progression in surgery, allowing readers to better understand its current state and potential future developments.…”
Section: Discussionmentioning
confidence: 99%
“…Division of Plastic & Reconstructive Surgery, Indiana University School of Medicine, Indianapolis, IN; 2 Department of Plastic and Reconstructive Surgery, Memorial Sloan Kettering Cancer Center, New York, NY; 3 Department of Plastic and Reconstructive Surgery, University Medical Center Utrecht, Utrecht, The Netherlands; 4 Department of Plastic Surgery, Corewell Health, Grand Rapids, MI On 30 November 2022, ChatGPT, a state-of-the-art natural language-processing model was developed by OpenAI (San Francisco, CA, USA). 1 It elicits human-like conversations and can comprehend and respond to complex queries in natural language.…”
mentioning
confidence: 99%
“…The most notable example is artificial intelligence, which is already demonstrating potential benefits for surgical systems, 66 in particular those for general surgery. [67][68][69] For prehabilitation interventions specifically, artificial intelligence could assist with intervention personalisation according to patient characteristics and preferences, enhancement of information provision and experience for potentially improved adherence, 70 predictive metrics to allow for early modulation of interventions when required, 71 and decision aids 72 for both clinicians and patients. In studies that have drawn broad media attention, artificial intelligence chatbots have shown high levels of quality and empathy when providing clinical solutions for patient issues, 73 and these could potentially enhance patient communication approaches within prehabilitation interventions before general surgery.…”
Section: Discussionmentioning
confidence: 99%
“…El estudio reveló que aproximadamente 30% de las pacientes mostraron inconformidad con el resultado reconstructivo obtenido. 28 La identificación de factores de riesgo y la capacidad de predecir la satisfacción del paciente pueden ayudar a los cirujanos a tomar decisiones informadas y mejorar los resultados de los procedimientos de reconstrucción mamaria.…”
Section: Reconstrucción Mamariaunclassified